Transcriptome Profiling and Network Analysis Provide Insights Into the Pathogenesis of Vulvar Lichen Sclerosus - Wang, Lingyan; Lv, Qingqing; Guo, Jiayi; Wang, Jianwei; Pan, Jing (Frontiers in Genetics, 2022)
Vulvar lichen sclerosus (VLS) is a chronic inflammatory dermatosis that affects female anogenital skin. Although VLS is considered a T cell-mediated autoimmune disease, the diagnosis criteria, molecular mechanism, and universally accepted therapies for this disease remain largely unresolved. To explore disease pathogenesis and potential biomarkers, we performed an RNA-Seq-based transcriptome analysis to profile the gene expression of VLS lesions. Differentially expressed gene (DEG) analysis revealed profound changes in expressions of coding genes, microRNAs, and long non-coding RNAs. Pathway and network analysis suggested that T cell activation-associated genes, including CD3G, CD3D, CD8B, LAT, LCK, ZAP70, CCR5, CXCR3, CXCL9, CXCL10, and CXCL11, were highly expressed in VLS, while NR4A family genes (NR4A1, NR4A2, NR4A3), whose coding products inhibit T cell activity, were significantly downregulated, suggesting heightened T cell response in VLS. Neutrophil chemoattractant genes CXCL1, CXCL2, CXCL3, CXCL8, and their cognate receptor CXCR2 were downregulated, suggesting dampened neutrophil activity. We also found the downregulation of genes involved in cell cycle progression, including cyclins (CCNB1, CCNB2, CCNL1, CCNE1, and CCNK) and centrosome factors (CENPA, CENPE, CENPF, and CENPN), while microRNA-203a and let-7, microRNAs known to inhibit cell growth, were found to be upregulated. These data collectively indicate that cell proliferation in VLS is compromised. In sum, these findings comprehensively deciphered key regulatory genes and networks in VLS, which could further our understanding of disease mechanisms and point toward therapeutic strategies.